Pengelolaan Pemasaran Politik Digital: Studi Kasus Pilkada Bupati Wonosobo – Jawa Tengah 2024 - Kartono, Munir; Mustofa, Mustofa; Bonartua Hutapea, Edison (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the management of digital political marketing in the 2024 Wonosobo Regency Election (Pilkada), focusing on the Afif Nurhidayat–Amir Husein candidate pair. The digital era has reshaped political campaign strategies in Indonesia, positioning social media as a primary arena for interaction between candidates and voters. Using a qualitative descriptive approach through a single case study, data were collected from in-depth interviews with five key informants—campaign team members, political consultants, academics, and local observers—and through digital observation of candidates’ social media activities. The findings reveal that political marketing in Wonosobo operates within a hybrid model, integrating traditional and digital methods. Social media primarily serves as a tool for visibility and image-building but remains limited in mobilizing voter participation. The existing digital divide, especially in rural areas, constrains online campaign outreach, making face-to-face engagement the decisive factor in influencing voter behavior. This study underscores the need for adaptive political communication strategies that align with local socio-technological contexts, positioning digital platforms as complements rather than replacements for traditional campaigning.